The world of myth: An anthology - David Adams Leeming (1937- (Oxford Univ, 1990)
The book provides a sweeping anthology of myths. There are fascinating stories of great floods from the ancient Babylonians, Hebrews, Chinese, and Myans; tales of apocalypse from India, the Norse, Christianity, and modern science; myths of the mother goddess from Native American Hopi culture and James Lovelock's Gaia. The book compares and contrasts how various societies have addressed similar concerns, or have told similar stories